EXPLORING VOCATIONAL SCHOOL PRINCIPALS’ DIGITAL LEADERSHIP IN CULTIVATING SCHOOL DIGITAL CULTURE - Zahro, Khamilatul; Andriani, Dwi Esti; Raihan, Primus Devra (Universitas Negeri Surabaya, 2025)
The accelerating digital transformation in education highlights the strategic role of principals in cultivating sustainable digital culture, yet empirical evidence from vocational schools in developing countries remains limited. This study employs a qualitative exploratory design in five public vocational high schools (SMKs) in Yogyakarta, Indonesia, with 15 informants comprising principals, teachers, and administrative staff. Data were collected through in-depth interviews, observations, and document analysis, and analyzed thematically. The findings reveal six interdependent dimensions of digital leadership: vision and policy, digital learning, teacher professionalism, digital management, assessment and supervision, and responsiveness to social–ethical issues. Together, these dimensions illustrate how principals strategically integrate technology and organizational culture to enable holistic school transformation. Unlike previous studies that primarily emphasize teacher innovation or PLC mediation, this research highlights the broader organizational processes of fostering digital culture within vocational education. Theoretically, it advances educational leadership literature by proposing a context-specific framework for digital leadership in developing countries. Practically, it provides concrete guidance for principals and policymakers in designing professional development, formulating digital policies, and fostering ethical digital awareness to strengthen sustainable school digitalization.